Some of Behaviorism Choices that is Availability of Managerial Leaderships an affect of job frustration Management An Opinion Study of Heads Units and Departments In Modern Badoosh Cement Factory - خليف, سلطان احمد (Journal of Economics and Administrative Sciences, 2012)
Represent choices Behaviorism available to the Managerial leaders one of the prerequisites to run any beginnings of a psychological or dilemmas Managerial barriers to working in the field of work has been varied these options until it had taken several kinds of which contributed to the left different impacts on the alleviation of these problems, which prompted the researcher to raising the problem of study within the framework of questionable content how to contribute to that shown by Choices Behaviorism accredited to the Managerial leaders in the management of frustration job workers on-site field study and in reference to the importance of the statement of the main objective with the representatives of identifying the impact, which is dictated by the choices of the Behaviorism management of frustration job workers Badoosh new cement plant in the sample of heads of departments and people, has been the adoption of a number of statistical models (frequencies, percentages, standard deviations, correlation, regression). In that light has reached a number of conclusions, especially the presence of the impact of the choices Behaviorism approved by the Managerial leaders in the management of frustration career workers, prompting the researcher to go out several proposals, notably the need to activate the Choices Behaviorism web integrated in order to contain no cases frustrating at work.